2017
DOI: 10.1109/jbhi.2016.2524646
|View full text |Cite
|
Sign up to set email alerts
|

Motion Artifact Suppression in Impedance Pneumography Signal for Portable Monitoring of Respiration: An Adaptive Approach

Abstract: The focus of this paper is motion artifact (MA) reduction from the impedance pneumography (IP) signal, which is widely used to monitor respiration. The amplitude of the MA that contaminates the IP signal is often much larger than the amplitude of the respiratory component of the signal. Moreover, the morphology and frequency composition of the artifacts may be very similar to that of the respiration, making it difficult to remove these artifacts. The proposed filter uses a regularization term to ensure that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Therefore, the objective is to have more knowledge about thoracic bioimpedance changes and its relation with breathing movement and respiratory volume. The combination of accelerometer and bioimpedance measurements has been used before, however, these studies used the combination for motion aritifact removal 22,23 . These studies did not examine the relationship between these signals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the objective is to have more knowledge about thoracic bioimpedance changes and its relation with breathing movement and respiratory volume. The combination of accelerometer and bioimpedance measurements has been used before, however, these studies used the combination for motion aritifact removal 22,23 . These studies did not examine the relationship between these signals.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies showed acceptable validity and reliability for RR monitoring, but lower validity and reliability for TV and minute ventilation. Recently, researchers have constructed ambulatory impedance pneumography devices for quantitative monitoring of respiratory characteristics [13], and developed algorithms to remove motion artifact in impedance pneumography signals [23]. Further efforts have been made to develop new methods to estimate the RR from ECG and photoplethysmogram signals [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Ansai et al found that the adaptive filter based on N.L.M.S. algorithm was applied to remove motion artifacts in respiratory signals with an average error of only 4.72 [10]. Satyanarayana et al compared the noise interference of the adaptive filter based on LMS and N.L.M.S.…”
Section: Literature Review a The Releated Foreign Researchmentioning
confidence: 99%